(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Earlier, we judge the corporate success by its profit but now they need to perform green practices to create green environment which help to build loyalty. Corporation needs to reduces the carbon footprints and create positive the attitude of the employees towards social and environmental aspects. Green HRM help the organization to use the resources in an efficient way. Owner of the business are little but owner of the nature are many (community) where business and we survive. It is advantageous for both business the society. In India many firm adopt Green HRM which help in environmental sustainability like Wipro Technology, Suzlon Energy, ONGC, ITC Limited and many more.